Microbial community composition from 16s V4 region amplicon sequencing of the methane Seep at the Cinder Cones Cold Seep site, Nov 2016 - Andrew Thurber (Biological and Chemical Oceanography Data Management Office (BCO-DMO), 2019)
This dataset includes details on 151 marine sediment community samples collected from the Cinder Cones Cold Seep site [-77.8, 166.666] in the Ross Sea region, Antarctica in November 2016. Data are uploaded to the NCBI Sequence Read Archive under submission SUB2655615 [https://www.ncbi.nlm.nih.gov/bioproject/PRJNA387720] with a subset of the data from that archive originating from this project.